2017
DOI: 10.1177/1362361317703760
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sustained community employment among adults with autism and co-occurring intellectual disability

Abstract: Sustaining community employment is a challenge for adults with autism spectrum disorders, especially for those who have co-occurring intellectual disability, but factors contributing to this employment outcome have not been fully evaluated. This study utilized longitudinal data to explore the impact of contextual influences, family factors, and individual characteristics on sustained employment over approximately 18 months ( N = 105). Very few adults with autism spectrum disorder and intellectual disability ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 43 publications
1
63
0
Order By: Relevance
“…For those adults with ASD without an intellectual disability (ID), few had consistent employment in the community or consistently participated in PSE programs (although many are involved in these activities at a given point in time). Chan et al (2017) had similar findings for adults with ASD and ID; a very small percentage was consistently participating in community employment over the course of the study. In contrast, Howlin and colleagues (2013) found, in their long-term follow-up study, that most adults with ASD who were employed in their mid-20s were also employed in their 40s.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…For those adults with ASD without an intellectual disability (ID), few had consistent employment in the community or consistently participated in PSE programs (although many are involved in these activities at a given point in time). Chan et al (2017) had similar findings for adults with ASD and ID; a very small percentage was consistently participating in community employment over the course of the study. In contrast, Howlin and colleagues (2013) found, in their long-term follow-up study, that most adults with ASD who were employed in their mid-20s were also employed in their 40s.…”
supporting
confidence: 57%
“…For example, in the Taylor et al studies (Taylor et al 2015; Taylor and Mailick 2014), autism severity, IQ, and adaptive behavior were not associated with changes in vocational/PSE position over time (although they were associated with employment/PSE at a single point in time). Further, Chan et al (2017) found that an indicator of family functioning (maternal social support) was associated with sustained employment among adults with ASD, though family functioning tends not to be independently related to employment/PSE at one point in time. Thus, it is important to understand the characteristics related to vocational/PSE disruptions among youth and adults with ASD, as they may not be the same factors related to initially obtaining these positions.…”
mentioning
confidence: 92%
“…In addition to cognitive ability, past research has demonstrated that outcomes in autistic adults are associated with variegated factors, including demographics, severity of autism symptoms, co-occurring mental health symptoms, and subjective outcomes such as well-being or happiness. Independent living and employment were less likely to be achieved by adults of color or adults from more disadvantaged family backgrounds [Chan et al, 2018;Chiang, Cheung, Li, & Tsai, 2013;K. A. Anderson, Shattuck, Cooper, Roux, & Wagner, 2014].…”
Section: Ancillary Factors Associated With Adult Outcomesmentioning
confidence: 99%
“…Few studies to date have employed a multi-stakeholder qualitative approach. Most of the previous research on employment for persons with developmental disabilities has been driven by survey or population data [e.g., 9,27,[36][37][38][39][40][41] or from the perspective of a single stakeholder group [24,27,[42][43][44]. A better understanding of barriers relative to persons with developmental disabilities and employment from the multiple perspectives of a diverse group of stakeholders helps to inform future policies in the area of inclusive employment as well as to aid direct efforts to create more appropriate supports and resources.…”
Section: Introductionmentioning
confidence: 99%